Analytical Analysis of Common Fixed Point Results in Fuzzy Cone Metric Spaces - Tiwari, Surendra Kumar; Agrawal, Ranu (Asian Journal of Science, Technology, Engineering, and Art, 2024)
The concept of fuzzy sets was introduced by Zadeh (1965) which marked the beginning of the evolution of fuzzy mathematics. The introduction of uncertainty in the theory of sets in a non-probabilistic manner opened up new possibilities for research in this field. Since then, many authors have explored the theory of fuzzy sets and its applications, leading to successful advancements in various fields such as mathematical programming, model theory, engineering sciences, image processing, and control theory. In this paper, we aim to improve and generalize some common fixed point theorems in fuzzy cone metric spaces, an extension of the well-known results given by Saif Ur Rahman and Hong Xu-Li (2017).